Radical Scavenging and Anti-Inflammatory Properties of Pectin from Cissampelos pareira Linn. - WISIDSRI, Nakuntwalai; THUNGMUNGMEE, Suradwadee (Walailak Journal of Science and Technology (WJST), 2018)
Cissampelos pareira Linn. (C. pareira) has been used as a medicinal herb for treating fever and analgesic by Indian and Thai people. This experimental research investigates the scavenging ability of C. pareira pectin from leaves of variable concentrations on 2,2-diphenyl-1-picrylhydrazyl (DPPH) and nitric oxide (NO) free radicals, its anti-inflammatory property on lipopolysaccharide (LPS)-stimulated RAW264.7 macrophage cells, and the cell viability. The experimental results show that the DPPH and NO scavenging performances of C. pareira pectin are positively correlated to the pectin concentrations, with corresponding half maximal inhibitory concentrations (IC50)of 0.54 and 0.52 mg/ml. Meanwhile, the NO production in the LPS-stimulated macrophage cells is inversely correlated to the pectin concentrations. The cell viability in the LPS-stimulated macrophage cells is positively correlated to the C. pareira pectin concentrations, given the non-cytotoxicity of the extract compound. In essence, the inhibition of free radicals and the suppression of activated macrophages point to the usefulness of C. pareira pectin in functional dietary products and herb-based pharmaceuticals.